Short Communication: First report of the trematode Platynosomum illiciens (Trematoda: Digenea>/i>) in Felis catus in Costa Rica, Central America (Ciencias Veterinarias, 2021)
This paper is the first description of the trematode P. illiciens found in a domestic feline (Felis catus) in Costa Rica, detected as an incidental finding at necropsy. The cat’s carcass was accepted for a necropsy in the Pathology Service of the Veterinary Medicine School of the National University, Costa Rica. However, the origin and clinical history of this cat are unknown. Adult P. illiciens flukes were detected in the feline’s gallbladder. Species identification was conducted by morphological characterization and molecular sequencing analysis. Assessing the possible foci of this trematode in the country could be a useful tool to understand its cycle in Costa Rican mammals and birds and consider it as an organism capable of infecting and affecting the domestic feline population in the country.